Case Report: A Case of Infant Bronchial Dieulafoy's Disease and Article Review - Yang Chen; Yiting Mao; Xingfeng Cheng; Ruihua Xiong; Ying Lan; Feng Chen; Furong Zhang; Jun Liu; Yanting Wu (Frontiers Media S.A., 2021)
Background: Bronchial Dieulafoy's disease (BDD), characterized by constant diameter arterial malformation, is rare, especially among infants. The pathogenesis and clinical features of pediatric patients are unknown. Misdiagnosis and biopsy operations may lead to potential massive hemorrhage, which endangers the patient's life.Case Presentation: Here, we present a case of a 9-month-old boy who was diagnosed with BDD with massive hemoptysis. The boy was cured by embolization of the bronchial artery and was in good health at the 1-year follow-up. In addition, we searched PubMed, Google Scholar, and Web of Science databases using keyword "Bronchial Dieulafoy's Disease (BDD)" and found six additional cases of pediatric BDD.Conclusion: It is still insufficient to draw a conclusion about the origin of the disease. Bronchial angiography and endobronchial ultrasonography are considered promising methods to diagnose Dieulafoy's disease of the bronchus. Bronchoscopy with transbronchial biopsy should not be deployed due to the high risk of fatal hemorrhage. Explicit clinical case reports of BDD are needed to enhance the understanding of this rare disease.